Survey of Dermatologic Procedures in Transgender Adults. Issue 10 (18th October 2021) - Ragmanauskaite, Laura; Zhang, Qi; Kim, Jin; Getahun, Darios; Silverberg, Michael J.; Goodman, Michael; Yeung, Howa
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Dermatologists have the opportunity to provide medically necessary procedures, including laser hair removal, to transgender patients for gender affirmation. Further research is required to better assess the unique dermatologic needs of this population. OBJECTIVE: To examine the prevalence of dermatologic procedures among transgender people in the context of gender-affirming treatment. METHODS: This cross-sectional study examined survey responses from 696 transgender persons enrolled in the Study of Transition, Outcomes, and Gender cohort. Prevalence of self-reported dermatologic procedures was examined and compared across participant subgroups. RESULTS: Electrolysis was the most commonly reported procedure (32.9%). Transfeminine patients were more likely to use dermatologic procedures compared with transmasculine patients. Only 19 participants (2.8%) reported the use of dermal filler injections. CONCLUSION: Differences in utilization of dermatologic procedures were noted in transgender populations. Motivations, barriers, and optimal timing for gender-affirming dermatologic procedures among transgender persons should be examined in future studies.